Women's knowledge about pregnancy complicated by breast cancer and the attitude towards the implementation of anti-cancer therapy - Magdalena Jańczyk; Ilona Samek; Agnieszka Rolińska (Kazimierz Wielki University, 2019)
Introduction and purpose: Breast cancer is the most commonly diagnosed cancer during pregnancy. Women can treat it, but pregnancy has a significant impact on the types and duration of using treatment. Purpose is to present the opinions of women about pregnancy complicated by breast cancer. Material and methods: 206 women participated in the study. We used a survey on the Internet. The average age of the respondents was 31.2. To establish whether an observed frequency distribution differs from a theoretical distribution the chi2 test of goodness-of-fit was used, to estimate relation we use the chi2 test of independence. Results: There were statistically significant differences between the number of women who believe that breast cancer is benign vs. malignant. Most often indicated as a safe method of diagnosis in pregnant women were: biopsy, mammography with lead shield, ultrasound, there was also a relationship between the place of residence and the choice of biopsy and ultrasound. A significant difference was noted between the number of women declaring an attitude forward delay vs starting treatment in pregnancy. There was a significant relationship between the pregnancy experience and the declared decision on the time of beginning of the therapy. Conclusions: The results suggest that women are aware of the malignancy of breast cancer. Many of them incorrectly differentiate the effects of this cancer in pregnant women and not pregnant. Biopsy, mammography with lead shield, ultrasound are perceived as the safest methods of diagnosis. Significantly more respondents claim that they would postpone the therapy until the end of pregnancy. Women who have never been pregnant more often declare that they would decide to postpone treatment. Key words: breast cancer; pregnancy; attitude; knowledge.